Epidemiology and Clinical Features of COVID-19 among 4,015 Neonates in Iran: Results of the National Study from the Iranian Maternal and Neonatal Network - Schwartz, David A.; Mohagheghi, Parisa; Moshfegh, Fereshteh; Zafaranloo, Nazanin; Khalili, Narjes; Heidarzadeh, Mohammad; Habibelahi, Abbas; Ghafoury, Roya; Afrashteh, Fatemeh (American Journal of Perinatology, 2023)
Objective The coronavirus disease 2019 (COVID-19) pandemic had a significant impact on pregnant women and neonates in Iran. This retrospective study describes the national experience among neonates having suspected and confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection following hospital admission to examine the epidemiology, demographic, and clinical features.Study Design All nationwide cases of suspected and confirmed neonatal SARS-CoV-2 infection were drawn from the Iranian Maternal and Neonatal Network (IMaN) between February 2020 and February 2021. IMaN registers demographic, maternal, and neonatal health data throughout Iran. Statistical analysis of demographic, epidemiological, and clinical data were performed.Results There were 4,015 liveborn neonates having suspected or confirmed SARS-CoV-2 infection that fulfilled the study inclusion criteria identified in the IMaN registry from 187 hospitals throughout Iran. There were 1,392 (34.6%) neonates that were preterm, including 304 (7.6%) less than 32 weeks' gestation. Among the 2,567 newborns admitted to the hospital immediately after birth, the most common clinical problems were respiratory distress (1,095 cases; 42.6%), sepsis-like syndrome (355; 13.8%), and cyanosis (300 cases; 11.6%). Of 683 neonates transferred from another hospital, the most frequent problems were respiratory distress (388; 56.8%), sepsis-like syndrome (152; 22.2%), and cyanosis (134; 19.6%). Among 765 neonates discharged home after birth and subsequently admitted to the hospital, sepsis-like syndrome (244 cases; 31.8%), fever (210; 27.4%), and respiratory distress (185; 24.1%) were most frequent. A total of 2,331 (58%) of neonates required respiratory care, with 2,044 surviving and 287 having a neonatal death. Approximately 55% of surviving neonates received respiratory support, compared with 97% of neonates who expired. Laboratory abnormalities included elevations of white blood cell count, creatine phosphokinase, liver enzymes, and C-reactive protein.Conclusion This report adds the national experience of Iran to the list of reports from multiple countries describing their experience with COVID-19 in neonates, demonstrating that newborns are not exempt from COVID-19-morbidity and mortality.Key Points
Keywords: COVID-19; SARS-CoV-2; Iran; neonatal COVID-19; neonatal infection; coronavirus infection